2003
DOI: 10.1093/ajcn/78.3.660s
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of meat-based and plant-based diets and the environment

Abstract: Worldwide, an estimated 2 billion people live primarily on a meat-based diet, while an estimated 4 billion live primarily on a plant-based diet. The US food production system uses about 50% of the total US land area, 80% of the fresh water, and 17% of the fossil energy used in the country. The heavy dependence on fossil energy suggests that the US food system, whether meat-based or plant-based, is not sustainable. The use of land and energy resources devoted to an average meat-based diet compared with a lactoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
519
1
26

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 840 publications
(558 citation statements)
references
References 6 publications
12
519
1
26
Order By: Relevance
“…For instance, it should be noted that the ep-EROI values for the purse seining fleets included in this study are substantially lower than most of those collected in literature (Tyedmers 2001). Nevertheless, many of these fisheries are linked to landings that are destined for Troell et al (2004), h Pimentel and Pimentel (2003), i Unpublished, j Hospido et al (2003) fishmeal production, rather than direct human feeding, the latter being the case in the Galician fleets assessed. Galician offshore trawling and long lining fisheries, as far as we could ascertain through a comprehensive set of publications, constituted the fleets with lowest ep-EROI values, which highly questions the efficiency of these fleets in terms of energy return.…”
Section: Contextualization Of the Results And Comparison With Other Smentioning
confidence: 99%
“…For instance, it should be noted that the ep-EROI values for the purse seining fleets included in this study are substantially lower than most of those collected in literature (Tyedmers 2001). Nevertheless, many of these fisheries are linked to landings that are destined for Troell et al (2004), h Pimentel and Pimentel (2003), i Unpublished, j Hospido et al (2003) fishmeal production, rather than direct human feeding, the latter being the case in the Galician fleets assessed. Galician offshore trawling and long lining fisheries, as far as we could ascertain through a comprehensive set of publications, constituted the fleets with lowest ep-EROI values, which highly questions the efficiency of these fleets in terms of energy return.…”
Section: Contextualization Of the Results And Comparison With Other Smentioning
confidence: 99%
“…A landmark study acknowledging the multiple impacts of meat production on ecosystems is the report Livestock's Long Shadow by the United Nations Food and Agriculture Organization (FAO) (Steinfeld et al 2006; see also Steinfeld, 2009). With respect to meat consumption-which is not Livestock's Long Shadow's primary focus-there is a strong scholarly consensus that plant-based foods are much better from both environmental and energyefficiency perspectives than animal-based foods (e.g., Pimentel & Pimentel, 2003;2008;Duchin, 2005;Baroni et al 2007;McMichael et al 2007;Marlow et al 2009;Tukker et al 2011). Therefore, reducing the consumption of meat and dairy products (we will not focus on the latter here) is crucial for making our diets more sustainable and reducing the ecological footprint of food systems (Lang & Barling, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in productivity have compensated for some of the increases in land requirements. In addition, Pimentel & Pimentel (2003) examined the differences between meat-and plant-based diets, showing the higher impact of meat consumption measured in land use [in hectares (ha)], energy use [in kilocalories (kcal)] and water use (in liters). Consumption of food in the United States accounts for 50% of the total land, 18% of non-renewable energy sources, and 80% of water use.…”
Section: Measuring the Impact Of Food Consumption: A Literature Reviewmentioning
confidence: 99%
“…Consumption of food in the United States accounts for 50% of the total land, 18% of non-renewable energy sources, and 80% of water use. Pimentel & Pimentel (2003) found that a meat-based diet requires more embodied energy than a plant-based diet so they regard the latter to be more sustainable. The authors stated that American agricultural production is not sustainable, partly because it is based on excessive reliance on fossil fuels.…”
Section: Measuring the Impact Of Food Consumption: A Literature Reviewmentioning
confidence: 99%